2017
DOI: 10.3329/jom.v18i1.31172
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Gonadotropins in Infertile Men with Sertoli Cell Only Syndrome from Gaza Strip

Abstract: Abstract Abstract Abstract Aim: Aim: Aim: Aim: Aim: To assess serum testosterone and gonadotropins in Sertoli cell only syndrome patients from Gaza Strip.Methods: Methods: Methods: Methods: Methods: Based on testicular biopsy, a cross section of 74 Sertoli cell only syndrome patients were enrolled in the study. Age matched 44 fertile men were served as controls. Patients and controls were questioned for their medical history. Blood samples were drawn and serum testosterone, luteinizing hormone (LH), and follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
3
3
0
Order By: Relevance
“…In this study, patients with SCO had the lowest testosterone and highest FSH concentrations. This was in accordance with a previous study by Yassin et al [27],…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, patients with SCO had the lowest testosterone and highest FSH concentrations. This was in accordance with a previous study by Yassin et al [27],…”
Section: Discussionsupporting
confidence: 94%
“…In this study, patients with SCO had the lowest testosterone and highest FSH concentrations. This was in accordance with a previous study by Yassin et al [27], wherein lower testosterone (1.7 ± 1.3 vs. 5.0 ± 2.2 ng/mL; P <0.001) and higher FSH (20.8 ± 14.8 vs 7.7 ± 3.9 mIU/mL; P <0.001) concentrations were found in patients with SCO syndrome (SCOS) than in fertile men. Another study of 134 patients with SCOS also revealed low testosterone (4.4 ± 1.6 ng/mL) and high FSH (18.9 ± 9.0 mIU/mL) concentrations [28].…”
Section: Discussionsupporting
confidence: 93%
“…Infertility is a complex problem and associated with several factors such as hormonal, biological, genetic and lifestyle factors (Krausz & Chianese, 2014;Yassin, Lubbad, Taha, Laqqan, & Jamiea, 2017). About 15% of couples worldwide suffer from infertility problem (Inhorn & Patrizio, 2015), in addition, male infertility problems considered as a major cause of infertility in human couples (Anawalt, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Infertility has been generally defined as an inability to achieve pregnancy after 12 months of regular unprotected intercourse (Poongothai, Gopenath, & Manonayaki, ), and infertility is a complex disorder that may be a result of genetic, hormonal and environmental factors (Anawalt, ; Barazani, Katz, Nagler, & Stember, ; Ferlin & Foresta, ; Yassin, Lubbad, Taha, Laqqan, & Jamiea, ). Semen analysis is routine analysis, that is used to evaluate the male partner of the infertile couple (Boivin, Bunting, Collins, & Nygren, ; Tadeu Andrade‐Rocha, ) and 15% of couples around worldwide suffered from infertility problems (Kumar & Singh, ; Rives, ).…”
Section: Introductionmentioning
confidence: 99%